2017
DOI: 10.1108/intr-11-2015-0321
|View full text |Cite
|
Sign up to set email alerts
|

Creating e-shopping multisensory flow experience through augmented-reality interactive technology

Abstract: Purpose Drawing on virtual liminoid theory, the purpose of this paper is to examine factors that induce a multisensory flow experience in an e-shopping context through the use of augmented-reality interactive technology (ARIT). Design/methodology/approach To validate the research framework, a task-based laboratory study was performed. Participants were recruited through a snowball e-mail method and requested to freely and independently use ARIT for clothes fitting in the laboratory, after which they complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 80 publications
3
110
0
Order By: Relevance
“…A review of the literature also shows that the interconnection among the three components of the PAT model (person, artefact and task) can influence flow. For example, research has supported that immediate feedback on the progress of a task from the artefact system to the consumer explains how the linkage among the person, artefact and the task can lead to flow experience (Huang & Liao, 2017; Luna et al., 2002; Ozkara et al., 2017). Review reveals that the interconnection among the three factors of PAT has received the least attention from researchers.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature also shows that the interconnection among the three components of the PAT model (person, artefact and task) can influence flow. For example, research has supported that immediate feedback on the progress of a task from the artefact system to the consumer explains how the linkage among the person, artefact and the task can lead to flow experience (Huang & Liao, 2017; Luna et al., 2002; Ozkara et al., 2017). Review reveals that the interconnection among the three factors of PAT has received the least attention from researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Research indeed showed that increasing enjoyment while shopping online consequently enhances brand attitude and purchase intention (Javornik, 2016;Li and Meshkova, 2013;Pantano et al, 2017;Yim et al, 2017). At the same time, enjoyment while shopping online is characterized by feeling immersed and involved, which makes consumers less critical towards the content and more likely to be persuaded (Huang and Liao, 2017;Javornik, 2016;Yim et al, 2017). This can also translate into a higher willingness to disclose personal data.…”
Section: Hypothesis 3b (The Perceived Enjoyment Of the Consumer's Ownmentioning
confidence: 98%
“…Augmented Reality (AR) is one of the most promising emerging technologies and has found its way into the research field of education, entertainment, games, daily life, and marketing, etc. [1][2][3][4]. Today, AR technology has gradually matured and become a research hotspot and trend in the field of education [5,6].…”
Section: Introductionmentioning
confidence: 99%